An investigation of mechanical and acoustic absorption properties of multiaxial glass fiber and hazelnut's shell reinforced poliester resin composites - (:unkn) unknown (JVE INT LTD, 2009)
Sound absorption in living, traveling and working environment constitutes one of the major requirements for human comfort today. Sound insulation requirements in automobiles, in manufacturing environments, and in equipments, generating higher sound pressure, strives the need to develop more efficient and economical ways of producing absorption materials. Traditionally, economics of recent research has enforced the research to focus on industrial waste materials. Textile structures nowadays are widely used in technical application. Textile structures have many application areas because of their low density, low cost and high strength. Multiaxial warp knitted fabrics have excellent properties to improve the mechanical properties of composite structures because of various fiber direction opportunities. At the present times, recycling of waste materials come into question. The aim of this study is to use waste materials for producing reinforced composite structures. Composite layers produced with multi-axial knitted fabrics, hazelnut's shell and thermoset polyester resin. Priority was given to the investigation of acoustic absorption properties of composites which contain variety sizes of hazelnut's shell.
Keywords: Multi axial knitted fabrics; Composite materials; Hazelnut's shell; Acoustic absorption properties; Polyester composites; NON-CRIMP FABRICS; SOUND-ABSORPTION; TRANSMISSION LOSS; POROUS MATERIALS; ELEMENT